Implementation Analysis of Law 22/2022 for Inmates' Mental Health Rights at Gianyar Class IIB Detention Center - RS, Nurianto; Rendang, Dewa Ayu Ratih Wiranti; Suandika , I Nyoman (Ridwan Institute, 2025)
The right to mental health is a fundamental part of human rights that must be fulfilled by the state, including for correctional inmates. Mental health includes the ability of individuals to think, feel, and act adaptively in the face of life’s stresses. However, in the environment of the Class IIB State Prison in Gianyar, the fulfillment of this right has not run optimally. Various problems, such as the limited number of mental health workers, the absence of permanent psychologists, the lack of mental rehabilitation programs, and overcapacity conditions that trigger stress and conflicts between inmates, are the main inhibiting factors. This study examines the factors that affect the mental health of inmates and analyzes the implementation of Law Number 22 of 2022 concerning Corrections by health workers in Gianyar Prison. The method used is a normative juridical approach supported by empirical data through observation and interviews with healthcare staff and correctional officers. The results show that the implementation of these regulations has not been optimal, primarily due to vague normative formulations and the absence of clear technical standards related to mental health services. The practical implications include the urgent need for more operational regulations, adequate provision of psychological resources, and the integration of ongoing mental rehabilitation programs to fulfill inmates’ legal rights and support more effective social development and reintegration processes.